Microstructural and Genetic Insights Into the Formation of the “Winter Diffusion Layer” in Japanese Pearl Oyster Pinctada fucata and Its Relation to Environmental Temperature Changes - Sato, Kei; Setiamarga, Davin H. E.; Yonemitsu, Hiroshi; Higuchi, Keita (Frontiers in Ecology and Evolution, 2022)
Phenotypic plasticity in molluscan shell microstructures may be related to environmental changes. The ‘winter diffusion layer’ is a shell microstructure of the Japanese pearl oyster Pinctada fucata, and is an example of this phenomenon. In this study, we used P. fucata specimens with shared genetic background to evaluate the molecular aspects of this phenomenon. To detect the seasonal changes in shell microstructure and mineral composition, shells of multiple individuals were periodically collected and analyzed using scanning electron microscopy and Raman spectrophotometry. Our observations of the winter diffusion layer revealed that this irregular shell layer, located between the outer and middle layers, had a sphenoid shape in radial section. This distinct shape might be caused by the internal extension of the outer shell layer resulting from growth halts. The winter diffusion layer could be distinguished from the calcitic outer shell layer by its aragonitic components and microstructures. Moreover, the components of the winter diffusion layer were irregular simple prismatic (the outer and inner sublayers) and homogeneous structures (the middle sublayer). This irregular formation occurred until April, when the animals resumed their ‘normal’ shell formation after hibernation. To check for a correlation between gene expression and the changes in microstructures, we conducted qPCR of seven major biomineralization-related shell matrix protein-coding genes (aspein, prismalin-14, msi7, msi60, nacrein, n16, and n19) in the shell-forming mantle tissue. Tissue samples were collected from the mantle edge (tissue secreting the outer shell layer) and mantle pallium (where the middle shell layer is constructed) of individuals collected in January (winter growth break period), April (irregular shell formation period), and August (normal shell formation period). Statistically significant differences in gene expression levels were observed between mantle edge and mantle pallium, but no seasonal differences were detected in the seasonal expression patterns of these genes. These results suggest that the formation of the irregular shell layer in P. fucata is caused by a currently unknown genetic mechanism unrelated to the genes targeted in the present study.